Intensidade luminosa, jejum pré-coleta e tempo de estocagem de amostras de sangue de frangos de corte para análises bioquímicas - Wachholz , Lucas (2020)
The aim of the present study was to evaluate the effect of using the serum or plasma (sodium fluoride) treatments, the fasting time to which the chickens were subjected, the sample storage time at -20 ºC and the light intensity submitted to the birds on the concentrations of glucose, cholesterol, triglycerides, and activity of the enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma glut amyl transferase (GGT) from broilers at 45 days of age. Two studies were carried out, in the first 70 male broilers of 45 days of age were submitted to blood collections after 0, 2, 4, 6, 8, 10 and 12 hours of fasting and immediately after collection and at 30 and 60 days after collection, serum and plasma levels of blood parameters were determined. Serum glucose concentrations declined linearly at fasting time (P<0.01) while cholesterol concentrations (P<0.01) and plasma GGT activity (P<0.05) increased linearly for fasting time. Plasma glucose concentrations and ALT activity had a quadratic effect with respective maximum points at 3h and 57 minutes and 8h and 9 minutes of fasting. The of AST in plasma and serum is not influenced by the fasting and storage time, therefore, concentrations of triglycerides and serum GGT activity showed quadratic effects with respective minimum points at 8h and 44 minutes and 5h and 12 minutes of fasting. Serum GGT was higher at 60 days of storage. The glucose and ALT values showed their lowest concentrations and or activity at 30 days in relation to the immediate analysis and 60 days of storage. Cholesterol concentrations, AST and ALT activity were higher in serum than in plasma (P<0.01) and triglycerides were more concentrated in the plasma fraction. In this way, the determination the analyzes can be conducted in up to 60 days when the samples are stored at -20º. Measurements of cholesterol and triglycerides can be performed on samples stored for up to 60 days, but not influenced by the fasting time. In the second study, 140 male chickens separated in two environments (5 and 20 lux of lighting) were used and blood was collected from 10 birds from each environment in each fasting period (0, 2, 4, 6, 8, 10 and 12 hours), for the preparation of serum and plasma that were stored at -20º C for 0, 15, 30, 60 and 120 days, after which biochemical analyzes were performed. Serum glucose concentrations declined linearly 1.15 mg dL-1 every two hours of fasting and plasma glucose had a quadratic effect with a minimum point of 8 h and 13 minutes of fasting. The serum ALT activities showed a quadratic effect with a maximum point at 3 h and 46 minutes of fasting, but the plasmatic activities of ALT did not adjust to the regression models used. Serum GGT activities were not influenced by fasting times (P>0.05), while plasma activities decreased by 1.60 IU L-1 every 2 hours of fasting. AST activities were influenced by fasting (P<0.001) but were not adapted to the equation models used (P>0.05). The storage times showed a quadratic effect on glucose concentrations with respective maximum points in serum and plasma for 95 and 72 days. The serum triglyceride content increased linearly, but the plasma triglyceride concentrations do not show changes related to storage (P>0.05). The storage time caused a quadratic response over the serum ALT with a maximum point at 32 days of storage, while in the plasma form there was a minimum point at 93 days of storage. Cholesterol concentrations and GGT activity increased linearly over storage time. The concentrations of glucose, triglycerides, and activity of the enzymes AST and ALT were higher under the luminous intensity of 20 lux and the concentrations of cholesterol and GGT activity were higher with the use of 5 lux of luminosity. In view of the above, it appears that samples for analysis of AST can be stored in up to 120 days at -20ºC. The preferential use of serum samples is indicated for the analysis of glucose, cholesterol, triglycerides, AST, ALT and GGT, avoiding freezing, with a six-hour fast and when transcribing the results it is recommended to specify the light intensity when to which the birds are exposed.